Influence of host-specific and locally isolated multi-strain probiotics on piglet performance, mortality, inflammatory response, and gut microbiome - Katatikarn Sahatsanon; Panneepa Sivapirunthep; Korawan Sringarm; Chaiwat Arjin; Patipan Hnokaew; Kamon Chaweewan; Chanporn Chaosap (Animal Bioscience, 2025)
Objective This study aimed to assess the impact of host-specific and locally isolated multi-strain probiotics on piglet performance, mortality, inflammatory responses, and gut microbiome. Methods A total of 52 piglet litters-34 from Landrace sows and 18 from Large White sows-were allocated to two groups: a control group and a multi-strain probiotic group. The probiotic group comprised seven strains of lactic acid bacteria (MLAB): Lactobacillus brevis, Lactobacillus reuteri, Lactobacillus paraplantarum, Lactococcus lactis, Lactobacillus pentosus, Weissella cibaria, and Pediococcus pentosaceus. Each strain was included in equal concentrations, resulting in a final liquid mixture containing 109 colony forming units/mL. The MLAB group received the probiotics orally starting from 7 days of age until weaning at four weeks. Following weaning, supplementation continued via feed spraying for an additional four weeks. Results MLAB supplementation did not significantly affect piglet performance but showed a trend towards reducing the mortality rate (p = 0.06). It influenced the inflammatory response by upregulating the expression of anti-inflammatory cytokines interleukin (IL)-4 and IL-10 (p<0.05). Microbial community analysis indicated that MLAB supplementation increased both microbial diversity (Simpson index: p = 0.06) and species richness (Chao1 index: p = 0.02). Piglets receiving MLAB had a significantly higher abundance of the phylum Firmicutes (p<0.01) compared to the control group, while the abundance of the phylum Bacteroidota was markedly reduced (p<0.01). In addition, the relative abundance of the bacterial genera Prevotellaceae_NK3B31 (p<0.01) and Chlamydia (p = 0.03) was lower in the MLAB group. Conclusion Overall, these results suggest that while MLAB supplementation does not directly improve piglet growth performance, it has the potential to improve immune function and promote a healthier gut microbiota in weaning piglets, which could ultimately reduce mortality rates.